2000
DOI: 10.1053/joca.1999.0304
|View full text |Cite
|
Sign up to set email alerts
|

Activation of annexin II and V expression, terminal differentiation, mineralization and apoptosis in human osteoarthritic cartilage

Abstract: Human osteoarthritic chondrocytes adjacent to the joint space undergo terminal differentiation, release alkaline phosphatase-, annexin II- and annexin V-containing matrix vesicles, which initiate mineral formation, and eventually die by apoptosis. Thus, these cells resume phenotypic changes similar to terminal differentiation of chondrocytes in growth plate cartilage culminating in the destruction of articular cartilage in osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
183
0
10

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(203 citation statements)
references
References 55 publications
10
183
0
10
Order By: Relevance
“…Previous reports have indicated that the biologic changes in articular chondrocytes during OA progression are similar to those of endochondral ossification (4,5). Investigators have found a sequential change of PTHrP localized in articular cartilage during the progression of inflammatory and degenerative arthritis (39).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous reports have indicated that the biologic changes in articular chondrocytes during OA progression are similar to those of endochondral ossification (4,5). Investigators have found a sequential change of PTHrP localized in articular cartilage during the progression of inflammatory and degenerative arthritis (39).…”
Section: Discussionmentioning
confidence: 97%
“…In patients with OA, chondrocytes are known to be able to resume phenotypic changes such as those occurring in epiphyseal growth plates, where chondrocytes undergo the process of terminal differentiation from hypertrophy to mineral deposition to eventual apoptosis (4,5). Chondrocytes in OA express the marker proteins of hypertrophic chondrocytes, including annex-ins, alkaline phosphatase, and type X collagen, but not type II collagen (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is further supported by the effect of thrombin on osteopontin, as the thrombin cleavage site is near the integrin binding locus of the protein. It is likely that chondrocytes are capable of assuming a phenotype similar to the hypertrophic phenotype responsible for bone formation in the growth plate, particularly in the setting of osteoarthritis (Kirsch et al 2000). Thus, it is not surprising that mechanisms of matrix mineralization in articular chondrocytes are similar to that of bone cells under certain conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Chondrocyte hypertrophy is one of the characteristics of osteoarthritis (OA) (Kirsch et al 2000;Tchetina et al 2007; van der Kraan et al 2009), and therefore a potential therapeutic target. Also, various growth pathologies are associated with abnormal hypertrophy (Kuizon and Salusky 2004;Wilkie 2005;Zuscik et al 2002).…”
Section: Introductionmentioning
confidence: 99%